Water Quality Assessment Using Benthic Macroinvertebrates in a Periurban Stream (Cameroon) - Menbohan S, Foto; S, Tchakonte; Gideon A, Ajeagah; S. H, Zebaze Togouet; C.F, Bilong Bilong; T, Njiné (The International Journal of Biotechnology, 2013)
In order to assess the water quality of Nga stream, the right tributary of Mefou, physicochemical variables were coupled to benthic macroinvertebrates communities. Physicochemical results revealed a good health status of the Nga stream, with significant differences of conductivity observed between stations and months (P < 0.05). Of the 2553 individuals collected (4 phyla, 7 classes, 15 orders, 74 families and 117 genera), Arthropods (99.25%) was dominated by the class of Hexapods (63.85%), followed by Decapods (35.41%), which were mainly predominated by Atyidae family (34.86%). Ephemeroptera-Plecoptera-Trichoptera (EPT) group (14.69%) constituted 25 families and 42 genera. EPT/Chironomidae density ratio varied significantly between stations and months (P < 0.05), while a significant correlation existed between temperature and dissolved oxygen (P < 0.05), temperature and pH, ammonia and nitrites (P < 0.05), Decapods and dissolved oxygen and Ephemeroptera and low degradable organic matter (P < 0.05). The Sorensen’s similarity coefficient expressed a close resemblance between stations Nga 1 and 3 (76.09%) and Nga 1 and 4 (77.69%). Shannon and Weaver and Pielou index revealed a diversified and equal distribution of macrozoobenthos downstream. The rank frequency diagram situated station Nga 1 at the growth phase and Nga 2, 3 and 4 at the maturation phase. The Hilsenhoff index (3.30 - 4.96) indicates good to excellent water status. The results of Nga stream could present referential characteristics used to follow up the evolution status of streams in non anthropisized zones of Cameroon.